Hubungan Konsep Diri Akademik dengan Motivasi Berprestasi pada Remaja Awal yang Tinggal di Panti Asuhan di Denpasar - Prabadewi, Komang Diah Laxmy; Widiasavitri, Putu Nugrahaeni (Jurnal Psikologi Udayana, 2014)
Early adolescence is a period for self-concept formation. The self concept is a set of beliefs and feelings of the individual about their own, including physical characteristics, social, emotional, aspiration and achievement (Hurlock, 1999). Concerned with the need of achievement, adolescents need to develop their self-concept specially their academic self-concept as a particular provision in order to face a competition in the work world later. The self concept is not an innate factor, but it is learned and shaped by individual experience in dealing with others. That is equal with the academic self-concept. When a person living in a different situation with the general one, such as live in an orphanage, it can affect early adolescents in shaping their self-concept, at last it can affect their desire to achieve their achievement. According to these conditions, the researchers wanted to see whether there are relationships between academic self-concept and achievement motivation in early adolescents who lives in an orphanage. This study uses quantitative research methods which is correlation analysis method using product moment that involving 120 early adolescents orphanages as subjects that obtained by using sample taking technique simple random sampling . The result found in this research, there is a positive and significant relationship between academic self-concept and achievement motivation in early adolescents who lives in orphanages in Denpasar, which is indicated by the correlation coefficient (r) between the variables of self-concept and achievement motivation is 0.588 with p value 0.000 (p< 0.05), which means that the variable of academic self-concept and achievement motivation variables correlated significantly and positively and both of those are at moderate intensity   Keywords: self concept, academic self-concept, achievement motivation, orphanages, early adolescents